Optimization Study of Photovoltaic Cell Arrangement Strategies in Greenhouses - Yuzhe Qin; Qing Cheng (Energies)
The replacement of greenhouse surfaces with photovoltaic cells currently presents issues with internal shading and uneven illumination, which adversely affect crop growth and yield. Therefore, in order to improve greenhouse lighting by altering the arrangement of photovoltaic cells for greater economic and environmental benefits, four cities (Harbin, Shenyang, Nanjing, and Guangzhou) were selected for this study. Greenhouse models were established using the DesignBuilder software tool, focusing on the summer and winter growth stages of cherry tomatoes and strawberries. Two arrangements were employed—compact (CR) and checkerboard (BR)—to evaluate 18 scenarios based on power generation, illuminance uniformity, and temperature. Analysis revealed that, among the four cities, the checkerboard arrangement improved average illumination uniformity by 37.34%, 37.9%, 38.2%, and 35.8%, respectively, compared with the compact arrangement. Except for nine rows of photovoltaic cells in Guangzhou, the unit of area power generation of the schemes exceeded 80 kWh/m2 in summer, with excellent power generation efficiency. In winter, there was a relative decrease. Among the four cities, only Harbin reached seven rows of photovoltaic cells which produced more than 80 kWh/m2 under the unit of area of photovoltaic cells, while the other three cities achieved five rows. Strawberries are not suitable for growing in Harbin and Shenyang in winter. In addition to this, cherry tomatoes and strawberries in different regions and at different stages have the best arrangements for growth and for maximizing cost efficiency.